Growth hormone locus polymorphism in Ongole Grade and Fries Holland Grade bulls and its implications in the digestibility of feed - Maylinda, S.; Busono, W. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
This research aimed to analyze polymorphism of the growth hormone (GH) gene and its implication on digestibility of low and high quality feed. Forty bulls Ongole Grade (OG) and 30 bulls Fries Holland Grade (FHG) had been selected and subjected for an experiment to measure body weight gain, dry matter intake, feed efficiency and feed digestibility. The treatment was crude fibrous feed from various plants with a fibre weight of 15% (P1: low quality) and 22.5% (P2: high quality). The 389 bp of GH gene was amplified (F = 5'-CCCACGGGAGAGAATGAGGC–3'; dan R = 5'-TGAGGAACTGCAGGGGGPA-3') and digested using Msp1 restriction enzyme. Polymorphism between OC and HFC bulls was 45%. The FHG bulls' weight gain were significantly higher than of OC (P<0.05) at first to third week, but become similar (P>0.05) at fourth week. It was concluded that the polymorphism between FHG and OC was high and HFC have a growth response and feed efficiency higher than those of OC.